The heart of plastic: utilizing the Drosophila model to investigate the effects of micro/nanoplastics on heart function - Hohman, Alyssa M.; Sorensen, Rachel M.; Jovanovic, Boris; McNeill, Elizabeth M. (Frontiers in Toxicology, 2024)
Microplastics (MPs) and nanoplastics (NPs) have increasingly been found in the environment. Until recently, most MPs/NPs toxicological research has been done in aquatic systems resulting in a gap in knowledge regarding terrestrial systems. Plastics have been shown to enter the circulatory system of humans, and can accumulate within organs, little is known about the effect this has on health. Heart disease is the leading cause of death globally, so it’s critical to understand the possible impacts MPs/NPs have on the heart. The Drosophila model has been growing in popularity within the toxicology field, it allows for affordable and rapid research on the impacts of a variety of toxins, including plastics. Some research has examined toxicological effects of plastics on the fly, evaluating the effects on mortality, fecundity, development, and locomotion. However, no one has studied the effects on the Drosophila heart. We utilize the Drosophila model to identify the potential effects of oral exposure to polystyrene MPs (1 µm in diameter) and NPs (0.05 µm in diameter) particles on heart function. Flies were exposed to 1.4 × 1011 particles/d/kg of larvae for MPs and 1.2 × 1018 particles/d/kg of larvae for NPs from egg to pupal eclosion. Heart function was then analyzed utilizing semi-intact dissections and Semi-automatic Optic Heartbeat Analysis software (SOHA). Following exposure to MPs and NPs we see sexually dimorphic changes to heart size and function. This study highlights the importance of additional Drosophila MPs/NPs research to identify the molecular mechanisms behind these changes.